2018
DOI: 10.3390/su10114102
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Impact of Coal Fines Migration on Coal Core Water Flooding

Abstract: Coalbed Methane (CBM) has become an important gas resource in recent decades. The brittle property of coal matrix and overactive operation make the migration of coal fines inevitable. Blockage by coal fines that plugs flow paths is a non-negligible issue that results in a significant decline in gas production. By setting different experimental conditions with the following factors—coal fines concentration of the mixture displacing fluids, constant flow pump rate, inlet pressure, outlet pressure and confining p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…or attached to the edge of fractures with water flow; thus, the degree of blockage and the characteristic of coal fines decide the permeability variation. Larger particles (less than 120 mesh) are difficult to invade into the fractures, and most of them were only attached on the edge of fractures [42,43]. And for large particle size, the pores and throats between the particles are relatively bigger; thus, the degree of permeability damage is relatively weak.…”
Section: Geofluidsmentioning
confidence: 99%
“…or attached to the edge of fractures with water flow; thus, the degree of blockage and the characteristic of coal fines decide the permeability variation. Larger particles (less than 120 mesh) are difficult to invade into the fractures, and most of them were only attached on the edge of fractures [42,43]. And for large particle size, the pores and throats between the particles are relatively bigger; thus, the degree of permeability damage is relatively weak.…”
Section: Geofluidsmentioning
confidence: 99%
“…For drainage control, in accordance with the pulverized coal production, water production, and reservoir pressure of coalbed methane wells, different drainage control measures are applied at different drainage stages to achieve refined drainage. 14,15 Meanwhile, different well-washing measures are adopted for process management, and a powder-proof tail pipe or a wire-wound screen is connected to the pump suction port. 16,17 Although different pulverized coal control measures have been proposed, effective prevention and control of the generation and migration of pulverized coal in reservoirs have not been achieved yet.…”
Section: Introductionmentioning
confidence: 99%
“…16−19 velocity and confining pressure, the effect of coal fines output within a fracture was examined. 20,21 It was found that the production of coal fines was positively correlated with displacement velocity and negatively correlated with confining pressure. According to the stress state of coal fine particles in the fracture and wellbore, the mathematical model of coal fines deposition was established, and the critical velocity for different sizes of coal fines was calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of coal fines migration and production is mainly carried out by field and laboratory monitoring of the drainage process and by detecting the concentration of coal fines. , Coal fines generation and production are closely associated with coal petrography properties. , Numerical calculation methods, including Risnes, Morita, Weingarten, Bratli, and other algorithms, were employed to simulate coal fines production. However, due to the complex geological conditions of coal seams, the results of these methods could not describe the real coal fines migration. In this regard, many physical experiments with the help of fracture conductivity instruments were conducted. By changing the flow velocity and confining pressure, the effect of coal fines output within a fracture was examined. , It was found that the production of coal fines was positively correlated with displacement velocity and negatively correlated with confining pressure. According to the stress state of coal fine particles in the fracture and wellbore, the mathematical model of coal fines deposition was established, and the critical velocity for different sizes of coal fines was calculated. Under the conditions of different particle sizes, flow velocities, and pore characteristics, the relationship between coal fines migration and permeability was investigated by physical experiments. , It was found that the shedding of coal fines increased the porosity and permeability, while the deposition could reduce the porosity and permeability.…”
Section: Introductionmentioning
confidence: 99%